The Effect Of Staff Responsiveness, Classroom Management And Administrative Efficiency On Educational Service Quality In Higher Education Institutions - Mohzana; Tyahya Whisnu Hendratni; Lazuardy Alief; Rinovian Rais; Ilmi Noor Rahmad; Subhan Fathu Alam (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Higher education institutions determine Educational Service Quality through the combination of staff responsiveness and classroom management and administrative efficiency. The researchers conducted their study through a quantitative method which used a survey to collect data from 150 active students who completed a questionnaire that was distributed through purposive sampling. The researchers employed multiple linear regression analysis to investigate how different variables interact through their separate and combined effects. The study results show that staff responsiveness and classroom management together with administrative efficiency create a substantial impact on Educational Service Quality. The three independent variables showed a positive impact which reached statistical significance for educational service quality. The research findings demonstrate that higher education service quality improves when staff members become more responsive and classroom management practices become better and administrative systems operate more efficiently. The study contributes to educational management research through its theoretical findings while providing higher educational leaders with practical methods to enhance service quality. The study results will help educational institutions establish their service quality standards because they define reference points for their educational service improvement strategies.